Pengaruh Struktur Modal terhadap Kinerja Keuangan Perusahaan PT Gowa Makassar Tourism Development Tbk di Kota Makassar Tahun 2019-2023 - Baso Erik; Abdi Akbar; Andi Mustika Amin; Zainal Ruma; Anwar Anwar (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study expects to decide the impact of capital construction on the monetary execution of PT Gowa Makassar The travel industry Improvement Tbk in Makassar City in 2019-2023. The examination utilizes an illustrative methodology. The number of inhabitants in this study is the yearly monetary report of PT Gowa Makassar The travel industry Improvement Tbk. The example of this study utilizes the monetary position explanation and benefit and misfortune articulation of PT Gowa Makassar The travel industry Advancement Tbk for the period 2019-2023. This study involves auxiliary information as fiscal reports for the 2019-2023 period obtained from www.idx.co.id. The information assortment strategy utilized in this study is documentation. The information examination method in this study utilizes numerous direct relapse investigation involving the Measurable Bundle for the Sociologies (SPSS) variant 25 program. The examination results show that the impact of capital design (DER, DAR, and LDER) somewhat and at the same time affects corporate monetary execution (ROE) at the organization PT Gowa Makassar The travel industry Advancement Tbk for the 2019-2023 period.